The advantage of being left-handed in interactive sports - Hagemann, N. (Attention, Perception, & Psychophysics, 2009)
As compared with their prevalence in the general population, left-handers are overrepresented in the expert domain of many interactive sports. This study examined to what extent this is due to negative perceptual frequency effects—that is, whether the greater frequency of tennis matches with right-handed opponents makes it possible to discriminate the stroke movements of right-handed players more precisely. Fifty-four right-handed and 54 left-handed males in three equal-sized groups of varying levels of tennis expertise (national league experts, local league intermediates, and novices) completed a tennis anticipation test in which they had to predict the subsequent direction of an opponent`s temporally occluded tennis strokes on a computer screen. The results showed that all three groups were better at predicting the direction of strokes by right-handed players. This supports the hypothesis that the overrepresentation of left-handers in the expert domain is partly due to perceptual frequency effects.